Essential elements of a city offer addressed to digital nomads: The perspective of territorial marketing - Sztuk, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The digital nomad lifestyle has become one of the fastest-growing trends in the labor market in recent years. Digital nomads, people settling in a city as its residents for several months before changing their location again, are active consumers of the city’s offer, which profits the host territorial unit. This specific group of customers requires designing a separate communication of the city offer, increasing the probability of choosing a given city as the next destination. The article aims to identify the significant elements of the city’s offer from the perspective of digital nomads. These data were collected based on the literature (scoping review method) and then summarized. The author identified key aspects related to the expectations of nomads towards the destination and the barriers encountered during the stay.
Keywords: city marketing; city offer; digital nomads